Minority representation in policing and racial profiling: A test of representative bureaucracy vs community context. Issue 4 (20th November 2017) - Shjarback, John; Decker, Scott; Rojek, Jeff J.; Brunson, Rod K.
Abstract : Purpose: Increasing minority representation in law enforcement has long been viewed as a primary means to improve police-citizen relations. The recommendation to diversify police departments was endorsed by the Kerner Commission and, most recently, the President's Task Force on 21st Century Policing. While these recommendations make intuitive sense, little scholarly attention has examined whether greater levels of minority representation translate into positive police-community relations. The purpose of this paper is to use the representative bureaucracy and minority threat frameworks to assess the impact of the racial/ethnic composition of both police departments and municipalities on disparities in traffic stops. Design/methodology/approach: A series of ordinary least squares regression analyses are tested using a sample of more than 150 local police agencies from Illinois and Missouri. Findings: Higher levels of departmental representativeness are not associated with fewer racial/ethnic disparities in stops. Instead, the racial/ethnic composition of municipalities is more predictive of racial patterns of traffic stops. Originality/value: This study provides one of the few investigations of representative bureaucracy in law enforcement using individual departments as the unit of analysis. It examines Hispanic as well as black disparities in traffic stops, employing a more representative sample of different size agencies.